[PP.11.03] MICRORNA-21 AS A PROGNOSTIC MARKER OF IMPROVEMENT IN ARTERIAL STIFFNESS IN WELL-CONTROLLED ESSENTIAL HYPERTENSION. (September 2016) - Marketou, M.; Parthenakis, F.; Kontaraki, J.; Patrianakos, A.; Nakou, H.; Touloupaki, M.; Vernardos, M.; Logakis, J.; Vougia, D.; Vardas, P.
Abstract : Objective: MicroRNAs (miRNAs) play a crucial role in myocardial and vascular remodeling and have emerged as potential diagnostic and prognostic biomarkers or as therapeutic targets. We aimed to investigate the expression profile of selected miRNAs in the peripheral blood of patients with well-controlled essential hypertension in relation to arterial stiffness. Figure. No caption available. Design and method: Expression levels of miRNAs miRNA-1, miRNA-133a, miRNA-26b, miRNA-208b, miRNA-499, and miRNA-21 in peripheral blood mononuclear cells were quantified by real-time reverse transcription polymerase chain reaction. Carotid femoral pulse wave velocity (cf-PWV) and carotid radial PWV (cr-PWV) were evaluated at baseline and after 1 year's effective antihypertensive therapy. Results: A total of 95 patients (50 men, mean age 62 ± 9 years) with well-controlled essential hypertension were included in the analysis. Only miRNA-21 was independently correlated with changes in both cf-PWV and cr-PWV (Figure 1), independently of blood pressure levels (r = -0.56 and r = -0.46, respectively; p < 0.001 for both). Conclusions: miRNA-21 is strongly associated with an improvement in arterial stiffness in patients with well-controlled essential hypertension, independently of their blood pressure levels. Our data highlight the significance of miRNA-21 in vascular remodeling and its role as a potential prognostic marker and future therapeutic target.